Development of Multi-Representation-Based Student Worksheet to Enhance Scientific Reasoning - Iwan Wicaksono; Sutarto Sutarto; Siti Nur Syuhada Musa; Imam Mudakir; Nuriman Nuriman (Universitas Lambung Mangkurat, 2026)
The capacity to engage in scientific thinking represents a significant challenge in the junior high school science curriculum, particularly with regard to comprehending concepts in a profound and systematic manner. The objective of this research is to develop and evaluate the feasibility of multi-representation-based student worksheets in enhancing students' scientific reasoning abilities. The research subjects consist of 120 junior high school students spread across the former Besuki region, including the Jember, Banyuwangi, Bondowoso, and Situbondo districts. The research was conducted employing the Research and Development technique via the 4-D model. This approach entailed the following: expert validation, implementation observations, effectiveness testing through pre-test and post-test tests, and student response questionnaires. The results demonstrated that the developed student worksheets exhibited a validity level of 83.7% (high) and a practicality of 78.5% (good), and effectiveness was demonstrated by an increase in the N-gain value of 0.57 (moderate) and a positive student response of 81.28%. Consequently, the utilization of multi-representation-based student worksheets has been demonstrated to enhance the learning of students. This finding underscores the value of adopting such material on a broader scale within the context of science education. It is recommended that future research be conducted at different grade levels and with a more diverse array of materials.